An earth-friendly herbal pesticide from Pongamia pinnata L. - Tripathi, Akanksha; Singh, Neha; Misra, Markandey; Dwivedi, Himanshu D; Dubey, N K (Current Botany, 2012)
Today use of hazardous chemical pesticides is a major environmental problem in global agriculture. The large scale use of these pesticides is degrading soil quality, underground and surface water quality, food quality of products. Herbal pesticides are a potential option for their chemical counterparts. It was observed that the crop fields where Pongamia pinnata trees are planted, there is less or no infestation of various insect-pests round the year.The trees of Pongamia pinnata are found allover India and the use of Pongamia as pesticide is cost effective, environment friendly and is in the reach of common villagers and farmers of India.